Perfusion with carbon monoxide does not affect extracellular glutamate in dialysates of the hippocampus of freely moving mice. (3rd April 2018) - Ito, Asuka; Jamal, Mostofa; Ameno, Kiyoshi; Tanaka, Naoko; Takakura, Ayaka; Miki, Takanori; Kinoshita, Hiroshi
Abstract: Carbon monoxide (CO) produces several neurological effects, including cognitive, mood, and behavioral disturbance. Glutamate is thought to play a particularly important role in learning and memory. Thus, the present study was aimed at investigating the local effect of CO on the glutamate level in the hippocampus of mice using in vivo reverse microdialysis. Mice were perfused with Ringer's solution (control) or CO (60–125 μM) in Ringer's solution into the hippocampus via microdialysis probe. Dialysate samples were collected every 20 min, and then analyzed with high-performance liquid chromatography coupled to an electrochemical detector. The result revealed that the perfusion with CO had no significant effect on glutamate levels ( p = 0.316) as compared to the control group. This finding does not support a local CO rise as the cause of the increased glutamate level in the hippocampus of mice.